Kierunki rozwoju rynku medialnego - Stuglik, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The new media progress depends on growing technology level in each media structure. To increase a number of consumers, media have to be more accessible, more mobile and more personal. To achieve this target, media use new equipment and new ideas. In this presentation the author explains this process using a few examples:1 Video on demand – called VOD;2 Mobile television;3 Webcasting.
Keywords: nowe media; technologia; wideo na żądanie; teelwizja mobilna; webcasting